Gold nanoparticle-mediated signal amplification of liquid crystal biosensors for dopamine. Issue 4 (28th January 2019) - Nandi, Rajib; Loitongbam, Lisha; De, Joydip; Jain, Varsha; Pal, Santanu Kumar
Abstract : A new design was developed for detection of dopamine using a boronic acid based amphiphile at aqueous–liquid crystal interface. The detection was highly enhanced in presence of gold nanoparticles. Abstract : A unique design strategy was developed for the detection of dopamine using a newly synthesized amphiphile containing boronic acid head group at the aqueous–liquid crystal (LC) interface. The optical signal of LC for the detection of dopamine was highly amplified in the presence of functionalized gold nanoparticles.